2012
DOI: 10.2527/jas.2010-3266
|View full text |Cite
|
Sign up to set email alerts
|

Apparent total tract energy and macronutrient digestibility and fecal fermentative end-product concentrations of domestic cats fed extruded, raw beef-based, and cooked beef-based diets

Abstract: The objectives of this study were to determine differences in apparent total tract energy and macronutrient digestibility, fecal and urine characteristics, and serum chemistry of domestic cats fed raw and cooked meat-based diets and extruded diet. Nine adult female domestic shorthair cats were utilized in a replicated 3 × 3 Latin square design. Dietary treatments included a high-protein extruded diet (EX; 57% CP), a raw beef-based diet (RB; 53% CP), and a cooked beef-based diet (CB; 52% CP). Cats were housed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 26 publications
10
48
0
Order By: Relevance
“…Apparent digestibility of energy and crude protein was also higher in dogs fed the meat diet. This is in agreement with previous studies in cats that have shown that both raw and cooked beef diets result in higher apparent total tract dry matter, crude protein, crude fat and gross energy digestibility compared to extruded (kibbled) diets (Kerr et al, 2012). …”
Section: Discussionsupporting
confidence: 93%
“…Apparent digestibility of energy and crude protein was also higher in dogs fed the meat diet. This is in agreement with previous studies in cats that have shown that both raw and cooked beef diets result in higher apparent total tract dry matter, crude protein, crude fat and gross energy digestibility compared to extruded (kibbled) diets (Kerr et al, 2012). …”
Section: Discussionsupporting
confidence: 93%
“…Total tract apparent CP and fat digestibilities of the dogs in the present study were similar to findings of previous raw meat studies [2][3][4]35 in cats (CP digestibility, 92.9 to 93.9; fat digestibility, 93.9 to 95.5) performed in the same laboratory. The digestibility of raw meat is much greater than that typical of kibble.…”
Section: Discussionsupporting
confidence: 89%
“…34 When a nonfermentable fiber source was included in a raw diet for cats, low fecal consistency scores were observed (2.1/5; hard feces). 2 When a more fermentable fiber source was included in those diets, ideal fecal scores were observed (3/5; typical feces), suggesting a fermentable fiber source should be included in raw meat-based diets, particularly for cats prone to constipation. High dietary ash content of such diets may also contribute to hard, dry feces.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…poultry species can act as a reservoir for pathogenic Salmonella species without overt signs of infection) ( 20 ) . Although the diet samples tested herein were negative for Salmonella , Kerr et al ( 10 ) detected Salmonella in 1–3-d-old chicks obtained from the same supplier. Whole-prey diet items containing gut contents make it inevitable that the animals ingesting them will be exposed to foreign bacteria.…”
Section: Discussionmentioning
confidence: 69%